Variabel Antecedent Orientasi Pasar dan Pengaruhnya terhadap Kinerja Bank Perkreditan Rakyat (BPR) (Studi pada Bank Perkreditan Rakyat di Jawa Timur) - Ni Nyoman Suarniki (Jurnal Aplikasi Manajemen, 2011)
The purpose of study is to provide valuable information to BPR as Director’s consideration in conducting strategic operations, in order to be able to stay competitive and obtain high profitability. There are 141 Rural Bank (BPR) in East Java areas, which the Directors served as the respondent to the questionnaire. Relationships among the variables were analyzed using Structural Equation Modeling (SEM., AMOS 6), based on primary data available through questionnaire and unstructured cross-sectional interviews to executive’s of BPR. Result of the analysis showed that Executive’s Characteristics, Inter-individual relationships, and Organization system as market orientation antecedent have a significant positive impact to BPR market orientation. Market orientation itself provided significant positive impact to BPR’s performance. Market changes as external factors has significant influence on market orientation and its effect to performance. Competitive Intensity is proved as external variable which had an interaction to market orientation effect to BPR’s performance. The impact of competitive intensity differed when it was perceived as high or low. In the interaction model, when competition is perceived as low, market orientation will provide significant positive impact towards performance, and when competition is perceived as high, market orientation will only provide insignificant impact. This implied that severe competition may pose threat to Company’s sustainability. Government policies, as the third external variable in this research also have significant interaction with internal variables (market orientation) to deliver performance. Government regulation had not strengthen the impact of market orientation towards performance, as reflected on the result of this research, 80 out of 141 respondent (57%) claimed that many of government policy related with BPR operations had still become a burden, it’s related to the weakness of BPR.Keywords: antecedent; market orientation; performance; external factors